Pengaruh Perbedaan Kecepatan Penarikan Tali Kolor (Purse Seine) terhadap Hasil Tangkapan Ikan di Perairan Tambak Rejo Blitar - Muhammad Iqbal Ananta; Yusrudin Yusrudin; Exist Saraswati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Purse seine is a fishing tool used to catch surface fish that are grouped and pulled towards the light. It works by encircling schools of fish with a net to create a vertical wall that blocks the fish's ability to move horizontally. The aim of the research is to find out how the speed of pulling the drawstring (purse line) affects the number of fish caught in Sampang waters. The research method used was an experimental method, namely by conducting experiments and monitoring the treatment carried out on purse seine fishing gear on mackerel fish caught in Sampang waters. The results of test 1 show that the results of catching mackerel fish in the catches from 3 treatments and 9 repetitions were very significantly different, so it can be concluded that from the results of the fishing experiment with a purse seine, drawstring speed had a very significantly different effect.